МАГНИТНОЕ ПОЛЕ В ЗАЗОРЕ ТОРЦЕВОГО ДУГОСТАТОРНОГО АСИНХРОННОГО ДВИГАТЕЛЯ С ПАРАЛЛЕЛЬНЫМ ВКЛЮЧЕНИЕМ ОБМОТОК ПРОТИВОПОЛОЖНЫХ СТАТОРОВ - Крищук, Р.С. (Інститут електродинаміки НАН України, Київ, 2016)
The paper is concerned with the method of calculation of the magnetic field in the gap of the axial arc-stator induction motor (AAIM) with disc rotor. It is reported that the longitudinal, transverse and thickness of the edge effects are takes into account. It draws our attention to uncompensated and compensated coil with the real placement of the slots and front parts. It should be noted that the equations of the current load of each stator are presented. It allows to calculate the engine with parallel windings in the opposite stators network. The following conclusions are drawn the real distribution of the magnetic field in the gap with the implementation of inverse to integral transformations. References 5, figures 2.